Association of psoriasis and/or psoriatic arthritis with autoimmune diseases: the experience of two Italian integrated Dermatology/Rheumatology outpatient clinics. (16th April 2015) - Carubbi, F.; Chimenti, M.S.; Blasetti, G.; Cipriani, P.; Musto, A.; Fargnoli, M.C.; Perricone, R.; Giacomelli, R.; Peris, K.
Abstract Background The systemic nature of psoriasis and its association with arthropathy, metabolic syndrome and cardiovascular disease is well established. In contrast, the association between psoriatic disease and other autoimmune disorders is still a matter of debate and data available in the literature are scarce. Objective The aim of this study was to examine the association of common autoimmune diseases (ADs), specified a priori, in an Italian cohort of patients affected by psoriasis and/or psoriatic arthritis (PsA), referred to two integrated Dermatology/Rheumatology outpatient clinics, over a 3‐year period. Methods Five hundred and two patients, affected by plaque psoriasis, PsA 'sine psoriasis' or a combination of psoriasis and PsA and with a diagnosis of at least one AD, were retrospectively evaluated. Univariate and multivariate binary logistic regression was employed to identify possible association between psoriasis, PsA, psoriasis‐PsA and ADs, by calculating corresponding odds ratios and 95% confidence intervals. Results Patients with psoriasis or PsA may develop one or more autoimmune diseases during their lifetime, with a higher prevalence of most ADs in psoriasis subgroup. We demonstrated for the first time that the combination of psoriasis‐PsA appears to be protective towards some autoimmune diseases. However, a gender effect should always be considered due to the different distribution of autoimmune disorders between males and females. Conclusion The new concept of psoriatic disease, focusing on genetic and molecular aspects which are at the basis of the pathogenesis of psoriasis and its related manifestations, extended the traditional idea of a disease confined to skin and joints. In this context, the multidisciplinary assessment of patients in the combined Dermatology/Rheumatology outpatient clinics would allow to identify early clinical and laboratory abnormalities not limited to skin and joint.